Strategi Pengembangan Potensi Ekowisata Mangrove Polaria Tanjung Pagar Menjadi Produk Wisata Kreatif Menggunakan Metode Analisis SWOT dan Analytic Hierarchy Process (AHP) - Istikoma, Istikoma; Surya, Rizki Surtiyan (IAI Nasional Laa Roiba Bogor, 2025)
Mendalok Village has a tourist area called the Tanjung Pagar Polaria Mangrove Ecotourism. The ecotourism is no longer developing due to the impact of Covid 19 and coastal abrasion so that it is not managed optimally and has an impact on the tourist location being deserted by visitors. Four criteria form the analysis using the Analytic Hierarchy Process (AHP). The ranking is based on how much each aspect influences the growth of mangrove ecotourism, and the objectives and weights are determined using objectives, criteria, and alternatives. The results of the scoring are obtained from multiplying the weight by the rating resulting in a score on the criteria of Improving Community Living Standards (MTHM) of 0.82%, Mangrove Ecosystem Sustainability (KEM) of 0.26% and Human Resources (HR) 0.06% and Creating Jobs (MLK). External components (opportunities and threats) and internal (strengths and weaknesses) of the project or organization are evaluated using the SWOT method. According to the study, there is a physical carrying capacity of 59 individuals per day and the mangrove ecotourism area has the potential to grow on an area of 10 hectares. Ten hours have been allocated for operations by management.